Islamic Finance and Accounting Standards in the UK: A Political Perspective - Munfariha, Siti Solihatul (ITB AAS INDONESIA Surakarta, 2024)
Purpose: This research aims at exploring the needs of accounting standards in the UK A Political Perspective as to whether they require a set of standars either under IFRS or other specific standards. Methodology: Systematic Literature Review is adopted in this research to summarize previous studies with the subject of accounting and halal restaurants. The SLR steps are identified and carried out throughout the study to arrive athe the analysis. Findings: The research findings reveal that there is a huge need of applying a specific accounting standard in the UK a Political Perspective. As the demand for Sharia-compliant financial products and services grows, there is a need for a robust accounting and regulatory framework to govern this industry. the process of setting standards for Islamic finance and accounting in the UK is not merely a technical exercise; it is deeply influenced by political factors and power dynamics. Originality: We bring to light some key issues that may pose important recommendation to the accounting standard setter such as in this case United Kingdom Accounting Standards.